2013
DOI: 10.1017/s1752971913000225
|View full text |Cite
|
Sign up to set email alerts
|

Trading control: national fiefdoms in international organizations

Abstract: According to principal-agent theory, states (the principals) delegate the implementation of a legalized agreement to an international organization (the agent). The conventional wisdom about states’ capacity to control international organizations is that differences among the member states impede control and consequently enhance the agent's autonomy, whereas agreement allows for effective control and limited autonomy. Contrary to this conventional wisdom, this article argues that conflicts among states need not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…While the Commissioners are officially neutral, scholars have shown that having "their commissioner" allows the member states to protect their interests during the actions of the agent (Wonka 2007;Thomson 2008). Likewise, Kleine (2013) argued that this mirroring nature of the College allows member states to exchange control over policy areas, creating "national fiefdoms" inside the Commission, which increases their grip on the agent. Similar delegation structures, in which all member states have representatives, are also common in the board of the agencies of the EU.…”
Section: Resultsmentioning
confidence: 99%
“…While the Commissioners are officially neutral, scholars have shown that having "their commissioner" allows the member states to protect their interests during the actions of the agent (Wonka 2007;Thomson 2008). Likewise, Kleine (2013) argued that this mirroring nature of the College allows member states to exchange control over policy areas, creating "national fiefdoms" inside the Commission, which increases their grip on the agent. Similar delegation structures, in which all member states have representatives, are also common in the board of the agencies of the EU.…”
Section: Resultsmentioning
confidence: 99%
“…Substantive reform after the Cold War became inevitable for the survival of the alliance. To use the a popular phrase from a US senator, NATO had to go "out-of-area or out of business" (Lugar 1993 (Kleine 2013), while lower positions may be subject to geographical balance. Third, contract policy also affects control with staff on permanent contracts having more autonomy than 'temporaries' or 'secondees' (Trondal 2006;Trondal, van den Berg and Suvarierol 2008).…”
Section: Functionalism Multiple Principals and Institutional Reformmentioning
confidence: 99%
“…It is useful to shortly discuss these senior posts further, as they are an important way for the member states of exerting influence (Kleine 2013 This article has shown that institutional form does not automatically follow function.…”
Section: Reforming the Nato Secretariat After The Cold Warmentioning
confidence: 99%
“…By identifying the distribution of positions in the Secretariat, we provide an objective measure across all nations of a zero-sum dimension of power, the power to control international institutions (Bachrach and Baratz, 1962;Barnett and Duvall, 2005), that appears to be of significant concern to governments around the world. This method of comparing power across nations addresses some of the critiques in the literature on the empirical measurement of power, European Commission and NATO (Kleine, 2013), and increasing evidence suggests that the national identities of bureaucrats affect the decision-making of institutions (Kaja and Werker, 2010;Johns, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One is the study of how individual nations exert influence within international institutions (Robert and Jacobson, 1973). Much of the recent work in this field focuses on the role of major powers in shaping outcomes including loans, agendas, concessions, votes, or peacekeeping scope (Allen and Yuen, 2013;Kaja and Werker, 2010;Kilby, 2011;Kleine, 2013;Kuziemko and Werker, 2006;Lim and Vreeland, 2013;Stone, 2004). A small but growing area of literature takes advantage of the unique institutional environment of the United Nations to answer broader questions (Gartzke, 1998;Fisman and Miguel, 2007).…”
mentioning
confidence: 99%